2013
DOI: 10.1016/j.hlc.2013.05.637
|View full text |Cite
|
Sign up to set email alerts
|

The Safety Profile of Perflutren Microsphere Contrast Echocardiography During Rest and Stress Imaging: Results from an Australian Multicentre Cohort

Abstract: CEE is a safe investigation in a broad range of indications and clinical scenarios. AR are very rare, mild and transient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Subsequent observational studies refined (i.e., substantially weakened) the signal for the major events of death, myocardial infarction, and arrhythmias but supported a low risk of anaphylactoid reactions [12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The product label evolved dynamically in response to this accumulating information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent observational studies refined (i.e., substantially weakened) the signal for the major events of death, myocardial infarction, and arrhythmias but supported a low risk of anaphylactoid reactions [12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The product label evolved dynamically in response to this accumulating information.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies [12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] have demonstrated the safety of perflutren, focusing on death, cardiac arrhythmias, and myocardial infarction, including three studies that were specifically requested by the FDA [12][13][14]. The first was the CaRES (Contrast Echocardiography Registry for Safety Surveillance) study [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Minor adverse effects include back pain, headache, nausea and rash and can occur in 0.27-3.5% of cases. 36,37 Physical injury may be provoked by the heat released from microbubble destruction -indeed, this is the mechanism that is thought to underpin sonothrombolysis (see below). Although some investigators showed ventricular ectopy in association with microbubble destruction, arrhythmia has never been reported as a consequence of contrast use.…”
Section: Safetymentioning
confidence: 99%
“…40 More recent studies have echoed this safety profile including a prospective phase 4 study of contrast agent (Definity). 36,37 The groups causing the greatest consternation included the critically ill cohort, those with an ACS and those with pulmonary hypertension. Given the prevalence of multiple comorbidities in an aging population, these groups stand to gain the greatest benefit from MCE.…”
Section: Safetymentioning
confidence: 99%